Cambiemos political discourse in Córdoba: breaks and continuities in an electoral climate - Filippelli, Nerina (Universidad Nacional del Litoral, 2021)
2019 was crucial for the province of Córdoba that had, apart from the presidential elections, its own elections scene in which the province government was chosen. In national terms Cambiemos found in this district a key base that gave the party not only the votes that fueled its access to the National State but that also sustained its support, no matter the crisis, until the following presidential elections. However, in the governor elections in Córdoba Cambiemos had to face a consolidated opponent: the local «peronismo» that questioned its electorate capital. From a social semiotics perspective, that states that every social event has a meaning dimension that is constitutive (Verón, 1993), we postulate discourse analysis as a privileged access way to understand the current political times. We postulate some hypothesis about the work of meaning that was put into action by the candidate Mario Raúl Negri (Cambiemos) in the dispute for the governance of Córdoba. We postulate that the main Cambiemos discursive modalities were implemented overall and that at the same time, bearing in mind the local situation, some specific aspects were reconfigurated.